Detail Desain Development of Sand Medium Crackers Frying Machine Using Design for Assembly Method - Ramadhian, Fauzi; Rahayu, Mira; Syafriza, Teddy (International Journal of Engineering and Technology, 2019)
Product Design can influence the complexity of the production process. In production activities are various production processes, one assembly. The assembly process can be said to be important, because the time in the assembly and the number of components can affect the cost of production. Products that have a short assembly time and the number of components that can slightly reduce the cost of production. Product development using Design for Assembly (DFA) needed. DFA is the method used to obtain a design that has few component and assembly costs are low. This research will be conducted using the method of DFA on crackers frying machine with sand media. Frying machine is used to help craftsmen crackers during the frying process using sand media. Toasting is used tubular using the motor. By using DFA passing through several stages to develop concepts acquired in previous investigators, resulting outcomes in the form of detailed design frying pan with a number of fewer components, namely from 93 parts to 43 parts, assembly time is less that of 739.73 seconds to 330, 13 seconds and greater assembly efficiency is from 19.06% to 25.44%.Â